Comparing adsorption of bisphenol A and similar compounds in aqueous solution by syringe filters - Nathaniel Godby; Alfred Conklin (Adsorption Science & Technology)
Analyte loss during syringe filtration is often overlooked in quantitative analyses. Bisphenol A and similar compounds are being extensively examined for their toxicity. This study serves to characterize common syringe filters and their effects on analytical results. The adsorbance of bisphenol A and similar compounds by filter media made from cellulose acetate, nylon, and polytetrafluoroethylene was examined using UV–Vis spectroscopy. Samples of bis(4-hydroxydiphenyl)methane, bis(4-hydroxyphenyl)sulfone, 2,2-bis(3-methyl-4-hydroxyphenyl)propane, 4,4′-(propane-2,2-diyl)diphenol, 4-cumylphenol, and phenol were studied. Solutions were analyzed before and after filtration. Filter composition significantly affected analyte concentrations in the filtrate solutions.